Flow Channels Detected in SuperDARN Longyearbyen data 2016-2018 - Katie Herlingshaw (7489640) (2020)
The algorithm for detecting ionospheric flow channels (FCs) described in Herlingshaw et al., 2019 ( https://doi.org/10.1029/2019JA026916 ) was applied to 2 years of SuperDARN Longyearbyen data (2016-2018). This pandas data frame provides information about the detected flow channels. The description of the variables inside are as follows: sd: start time and date ed: end time and date dur: duration [mins] rad: the radar code ('lyr' for all in this dataset) by: a 15 minute average of the interplanetary magnetic field By component before the start time of the FC [nT] bz: a 15 minute average of the interplanetary magnetic field By component before the start time of the FC [nT] clockAngle: the interplanetary magnetic field clock angle calculated using by and bz [degrees] alpha: angle used to easily plot the clock angle onto a polar grid [degrees] colat: the average magnetic colatitude of the center of the FC over the event [degrees] colatMax: the maximum magnetic colatitude of the center of the FC over the event [degrees] colatMed: the median magnetic colatitude of the center of the FC over the event [degrees] colatMin: the minimum magnetic colatitude of the center of the FC over the event [degrees] colatStd: the standard deviation of the magnetic colatitude of the center of the FC over the event [degrees] mlat: the average magnetic latitude of the center of the FC over the event [degrees] mlatMax: the maximum magnetic latitude of the center of the FC over the event [degrees] mlatMed: the median magnetic latitude of the center of the FC over the event [degrees] mlatMin: the minimum magnetic latitude of the center of the FC over the event [degrees] mlatStd: the standard deviation of the magnetic latitude of the center of the FC over the event [degrees] mlt: the average magnetic local time of the center of the FC over the event mltMax: the maximum magnetic local time of the center of the FC over the event mltMed: the median magnetic local time of the center of the FC over the event mltMin: the minimum magnetic local time of the center of the FC over the event mltStd: the standard deviation of the magnetic local time of the center of the FC over the event mltPlt: the angle used to easily plot the average magnetic local time of the center of the FC over the event on a polar grid mltMaxPlt: the angle used to easily plot the maximum magnetic local time of the center of the FC over the event on a polar grid mltMedPlt: the angle used to easily plot the median magnetic local time of the center of the FC over the event on a polar grid mltMinPlt: the angle used to easily plot the minimum magnetic local time of the center of the FC over the event on a polar grid mltStdPlt: the angle used to easily plot the standard deviation of the magnetic local time of the center of the FC over the event on a polar grid v: the average velocity of the FC over the event [m/s] vMed: the median velocity the FC over the event [m/s] vPeak: the maximum velocity of the FC over the event [m/s] vTrough: the minimum velocity of the FC over the event [m/s] vStd: the standard deviation of the velocity of the FC over the event [m/s] width: the average width of the FC over the event [km] widthMax: the maximum width of the FC over the event [km] widthMed: the median width of the FC over the event [km] widthMin: the minimum width of the FC over the event [km] widthStd: the standard deviation of the width of the FC over the event [km]